The Utilization of Burlap as a Creative Economy-Based Craft Art Learning Medium in Secondary Education: A Conceptual Study - Martaleny Kurnia Zazilah Putri; Fuji Astuti; Ardipal Ardipal; Heldi Heldi (V-art: Journal of Fine Art, 2026)
The use of local materials in art education has primarily been discussed in relation to creativity enhancement, yet limited scholarship systematically integrates such materials within a creative economy framework, particularly in secondary-level craft education. Existing studies tend to treat creativity as an isolated pedagogical outcome, overlooking its socio-economic and contextual dimensions. Addressing this gap, this study aims to develop a conceptual framework for goni (jute fabric) as a learning medium in craft education, grounded in creative economy principles at the secondary education level. This research employs a qualitative descriptive design, grounded in an integrative literature review of creativity theory, constructivist learning perspectives, and creative economy discourse. The analysis demonstrates that the material properties of goni—its texture, flexibility, accessibility, and economic value—enable the alignment of creative production with contextual economic literacy. This study contributes conceptually by articulating a pedagogical framework that links the utilization of local materials, the development of creativity, and awareness of the creative economy within craft learning. The formulation extends theoretical discussions on material-based art education and offers a structured basis for integrating creative economy orientation into secondary craft pedagogy.